The missing peace the inside story of the fight for Middle East peace - Ross, Dennis (New York Straus and Giroux, 2005)
he Missing Peace, published to great acclaim last year, is the most candid inside account of the Middle East peace process ever written. Dennis Ross, the chief Middle East peace negotiator in the presidential administrations of George H. W. Bush and Bill Clinton, is that rare figure who is respected by all parties: Democrats and Republicans, Palestinians and Israelis, presidents and people on the street in Jerusalem, Ramallah, and Washington, D.C.
Includes bibliographical references.
Keywords: Ross, Dennis